2013
DOI: 10.18388/abp.2013_2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ketamine, propofol, and ketofol on proinflammatory cytokines and markers of oxidative stress in a rat model of endotoxemia-induced acute lung injury.

Abstract: Intravenous lipopolysaccharide (LPS) leads to acute lung injury (ALI) in rats. The purpose of this study was to examine the anti-inflammatory and antioxidant efficacy of ketamine, propofol, and ketofol in a rat model of ALI. We induced ALI in rats via intravenous injection of LPS (15 mg kg -1 ). The animals were randomly separated into five groups: control, LPS only, LPS + ketamine (10 mg·kg -1 ·h -1 ), LPS + propofol (10 mg·kg -1 ·h -1 ), LPS + ketofol (5 mg·kg -1 ·h -1 ketamine + 5 mg·kg -1 ·h -1 propofol). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 43 publications
(37 reference statements)
3
19
0
Order By: Relevance
“…Ketamine treatment inhibits TNF production which may be due to inhibition of its synthesis or release. Our results parallel recent investigations showing anti-inflammatory properties of ketamine [24].…”
Section: Discussionsupporting
confidence: 92%
“…Ketamine treatment inhibits TNF production which may be due to inhibition of its synthesis or release. Our results parallel recent investigations showing anti-inflammatory properties of ketamine [24].…”
Section: Discussionsupporting
confidence: 92%
“…Propofol was previously reported to protect cells against oxidative stress induced by hydrogen peroxide (31,32), oxygen glucose deprivation (33) and endotoxemia (34), and to inhibit lipid peroxidation in various experimental cell models (35). The present results suggested that propofol significantly increased cell viability under normal culture conditions in a concentration-dependent manner, and the protective effects of propofol pretreatment against CoCl 2 hypoxiainduced injury were greatest at a concentration of 50 µg/ml.…”
Section: Discussionsupporting
confidence: 57%
“…Further, it is indicated that its neuroprotec-446 tive effects were mediated via anti-oxidative and anti-447 apoptotic properties (Krzisch et al, 2013). In the present 448 study, we reported that MT-3 was down-regulated by 449 Ang II, suggesting that Ang II caused hippocampal (Chen et al, 2010(Chen et al, , 2011Gokcinar et al, 2013). 461 However, the effects of propofol on the brain are quite Alzheimer's disease transgenic mice (Shao et al, 2014).…”
mentioning
confidence: 64%